Analisis sosial ekonomi usaha dagang kecil pecel lele di Kecamatan Telanaipura Kota Jambi - Iklima Raudatul Jannah; Heriberta Heriberta; Yohanes Vyn Amzar (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims: 1) to analyze the socio-economic conditions of small pecel catfish trading business in Telanaipura District, Jambi City. 2) to analyze the effect of length of business, working capital, age, education, and the number of dependents on the income of a small catfish pecel trade business in Telanaipura District, Jambi City. This research is quantitative research and the type of data used in this research is primary data in the form of cross-section data about the level of business income, length of business, working capital, age, education, and number of dependents. The sample in this study were all members of the population as a sample with a total of 37 respondents with the instruments used in the form of questionnaires and interviews. The data obtained were processed using SPSS 20 with the multiple linear regression analysis methods. The regression results show that partially only working capital and age variables have a significant effect on the business income of catfish pecel traders, while the length of business, education, and the number of dependents have no significant effect on the income of catfish pecel traders in Telanaipura District, Jambi City. Keywords: Business income, Business duration, Working capital, Age, Education, The number of dependents